Oxidative Cycloaddition of Aldoximes with Maleimides using Catalytic Hydroxy(aryl)iodonium Species. Issue 14 (24th May 2016) - Yoshimura, Akira; Nguyen, Khiem C.; Rohde, Gregory T.; Saito, Akio; Yusubov, Mekhman S.; Zhdankin, Viktor V.
Abstract: A mild catalytic procedure for the efficient oxidative cyclization of aldoximes with maleimides mediated by hypervalent iodine(III) active species has been developed. This catalytic cyclization affords the corresponding pyrrolo‐isoxazole products in generally good yields. The catalytic cycle involves active hydroxy(aryl)iodonium species generated in situ from 2‐iodobenzoic acid as precatalyst and m‐ chloroperoxybenzoic acid ( m ‐CPBA) as terminal oxidant in the presence of trifluoromethanesulfonic acid. The presence of active hydroxy(aryl)iodonium species in this reaction has been confirmed by ESI‐mass spectrometry and 1 H NMR spectroscopy. Abstract :